2007
DOI: 10.1097/cco.0b013e3280f00fe7
|View full text |Cite
|
Sign up to set email alerts
|

The role of taxanes and targeted therapies in locally advanced head and neck cancer

Abstract: Taxane/cisplatin/5 fluorouracil induction chemotherapy is clearly superior to cisplatin/5 fluorouracil. Epidermal growth factor receptor directed therapies can safely be combined with radiation and the combination shows encouraging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…32 The regional effectiveness of radiation can be enhanced by the accompanying radiosensitizing chemotherapy, including taxanes. 33 Thus, our results indicate that paclitaxel may synergize with IL13-PE38 in mediating antitumor activity in clinical trials as well.…”
Section: Discussionmentioning
confidence: 88%
“…32 The regional effectiveness of radiation can be enhanced by the accompanying radiosensitizing chemotherapy, including taxanes. 33 Thus, our results indicate that paclitaxel may synergize with IL13-PE38 in mediating antitumor activity in clinical trials as well.…”
Section: Discussionmentioning
confidence: 88%
“…Shortly after the turn of the millennium, Vermorken et al (5) demonstrated that the addition of docetaxel to cisplatin and 5-FU (DCF) in ICT followed by radiotherapy alone significantly increased locoregional control and survival with acceptable safety compared with ICT with cisplatin and 5-FU followed by radiotherapy alone in nonresectable SCCHN. These data and those from other studies (6)(7)(8)(9)(10)(11) have provoked renewed interest in the place of ICT in the treatment of SCCHN.…”
Section: Introductionmentioning
confidence: 76%
“…These trials evaluated regimens comprising the following: docetaxel plus cisplatin [20] or 5-fluorouracil [22]; paclitaxel, plus cisplatin [21] or carboplatin, plus 5-fluorouracil [23][24][25]; and paclitaxel plus 5-fluorouracil and oral hydroxyurea [26]. One phase III study was identified of paclitaxel plus cisplatin plus 5-fluorouracil induction chemotherapy in patients with locally advanced HNSCC [27]; preliminary data from Standard, and novel cytotoxic and molecular-targeted, therapies for HNSCC Murdoch 217 other, similar phase III trials are already available [28], with full results expected to be released soon.…”
Section: Resultsmentioning
confidence: 96%
“…Nonetheless, a recent clinical trend has seen increased use of taxane-based triple therapy (ie, docetaxel or paclitaxel, plus cisplatin or carboplatin, plus 5-fluorouracil [23][24][25]), and additional large-scale RCTs of such regimens are now warranted. One full paper of a phase III RCT of taxanebased triple therapy has been published [27]; preliminary data are available from other phase III trials [28], and full results are expected to be released soon. Other issues requiring large-scale RCTs are the potential places in therapy of the following: gemcitabine or vinorelbine, used alone or in various combination schedules; the recently developed EGFR-specific agent cetuximab in combination with radiotherapy, which is a good alternative to cisplatin-based chemoradiotherapy (mainly in patients with contraindications to cisplatin use), added to taxanebased triple therapy; erlotinib or gefitinib in patients with recurrent or metastatic HNSCC; and sequential schedules comprising induction therapy followed by chemoradiotherapy, with surgery reserved as a salvage approach.…”
Section: Resultsmentioning
confidence: 98%